2009
DOI: 10.1158/1535-7163.mct-09-0211
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid sensitizes human oral cancer cells to TRAIL-induced apoptosis through increase DR5 expression

Abstract: Suberoylanilide hydroxamic acid has been shown to selectively induce tumor apoptosis in cell cultures and animal models in several types of cancers and is about as a promising new class of chemotherapeutic agents. In addition, suberoylanilide hydroxamic acid showed synergistic anticancer activity with radiation, cisplatin, and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) in some cancers. Here, we report suberoylanilide hydroxamic acid also induced apoptosis in human oral cancer cells. Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Some conventional chemotherapeutic drugs, such as etoposide and doxorubicin, can induce apoptosis via DR5 upregulation in a p53-dependent manner. However, DR5 can also be regulated in a cell type-specific, trigger-dependent, and p53-independent manner, but the underlying mechanisms remain largely unclear [53,54]. Our data showed p53 was not associated with DR5 upregulation in ChK-treated OVCAR-3 and A2780/CP70 cells, which was in agreement with the previous study conducted in human ovarian cancer SKOV3 cells induced by CHM-1 [55].…”
Section: Discussionsupporting
confidence: 91%
“…Some conventional chemotherapeutic drugs, such as etoposide and doxorubicin, can induce apoptosis via DR5 upregulation in a p53-dependent manner. However, DR5 can also be regulated in a cell type-specific, trigger-dependent, and p53-independent manner, but the underlying mechanisms remain largely unclear [53,54]. Our data showed p53 was not associated with DR5 upregulation in ChK-treated OVCAR-3 and A2780/CP70 cells, which was in agreement with the previous study conducted in human ovarian cancer SKOV3 cells induced by CHM-1 [55].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, however, we also found that recombinant soluble TRAIL showed high cytotoxicity when added to OSCC cell lines. In line with our current results, it has been previously reported that treatment with TRAIL, used either alone or in combination with other drugs, resulted in induction of cell death in head and neck squamous cell carcinomas [24][25][26][27]. Taken together, our data clearly indicate that a high expression of TRAIL in OSCC cells, as observed both at immunohistochemistry and at flow cytometry, does not necessarily imply that OSCC cells are resistant to cytotoxicity induced by recombinant soluble TRAIL.…”
Section: Functional Expression Of Trail In Oscc Cell Linessupporting
confidence: 91%
“…The viability of OEC-M1 cells, SCC-4 cells, and HSC-3 cells were all reduced by compound 1a ; however, the killing effect of compound 1a on these cell lines might not be mediated by p53. In contrast to OEC-M1 cells, SAS cells have a high level expression of EGFR [26], and is resistant to TRAIL-induced apoptosis [27]. In this study, SAS cells were shown to be resistant to compound 1a treatment and we have yet to find the cause for this resistance.…”
Section: Discussionmentioning
confidence: 63%